2023
DOI: 10.1186/s12916-023-02761-6
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationship between gut microbiota and cancers: a two-sample Mendelian randomisation study

Abstract: Background Evidence from observational studies and clinical trials suggests that the gut microbiota is associated with cancer. However, the causal association between gut microbiota and cancer remains to be determined. Methods We first identified two sets of gut microbiota based on phylum, class, order, family, and genus level information, and cancer data were obtained from the IEU Open GWAS project. We then performed two-sample Mendelian randomisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(126 citation statements)
references
References 77 publications
0
92
1
Order By: Relevance
“…We used IVW and MR-Egger tests to assess heterogeneity, which was quantified by the Cochran's Q statistic, with heterogeneity considered significant if the p-value was less than 0.05. 28 The intercept term of the MR-Egger regression was used to determine the presence of pleiotropy, which if present in the IVs, that is, a p-value of less than 0.05, would lead to the assumption of exclusion and independence of the data not being valid and the results may not be robust, and the MR-PRESSO was also used to detect and correct for horizontal pleiotropy outliers in the MR test. 29 Additionally, we performed leave-one-out analysis to determine whether causal estimates were driven by any single SNP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used IVW and MR-Egger tests to assess heterogeneity, which was quantified by the Cochran's Q statistic, with heterogeneity considered significant if the p-value was less than 0.05. 28 The intercept term of the MR-Egger regression was used to determine the presence of pleiotropy, which if present in the IVs, that is, a p-value of less than 0.05, would lead to the assumption of exclusion and independence of the data not being valid and the results may not be robust, and the MR-PRESSO was also used to detect and correct for horizontal pleiotropy outliers in the MR test. 29 Additionally, we performed leave-one-out analysis to determine whether causal estimates were driven by any single SNP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to rule out potential limitations of MR analysis, for the associations of p ‐values < 0.05 in the IVW analysis of the individual GM and facial skin aging, we used sensitivity analysis to validate the robustness and reliability of the results by assessing the heterogeneity and pleiotropy of the data. We used IVW and MR‐Egger tests to assess heterogeneity, which was quantified by the Cochran's Q statistic, with heterogeneity considered significant if the p ‐value was less than 0.05 28 . The intercept term of the MR‐Egger regression was used to determine the presence of pleiotropy, which if present in the IVs, that is, a p ‐value of less than 0.05, would lead to the assumption of exclusion and independence of the data not being valid and the results may not be robust, and the MR‐PRESSO was also used to detect and correct for horizontal pleiotropy outliers in the MR test 29 .…”
Section: Methodsmentioning
confidence: 99%
“…8,9 Moreover, in non-metabolic conditions such as cancers, intestinal microbiota can be considered as a risk or preventive element. 10 However, limited attention was paid on the role of gut microbiota in ED in the past. It has been reported that gut microbiota diversity of ED patients was significantly different with healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…MR has proven to be a valuable tool in exploring causal association between complex traits or diseases and phenotypes. Recently, it has been applied to study the causal link between gut microbiota and various diseases, including mental disorders, 17 cardiovascular diseases, 18 and cancer 19 . In this particular study, we employed a two‐sample MR analysis to assess the potential relationship between gut microbiota and acne, using genome‐wide association study (GWAS) summary statistics from the MiBioGen consortium and FinnGen study.…”
Section: Introductionmentioning
confidence: 99%